STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PTKIS - Mumu Zainal Mutaqin; Solihin Solihin; Bambang Samsul Arifin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This study aims to analyze the effort to learn by determining learning strategies. As the goal of National Education which seeks to produce graduates who are professional in their fields and have moral character to be able to overcome various challenges in the life of the Nation today. The learning strategy of Islamic Religious Education needs to contribute and give more affirmation to students to be stronger in terms of faith, moral nobility and be able to create a dignified and happy nation in the hereafter. The research method used in this research is descriptive method. The type of data in this study consists of primary data, namely the collected data is accumulated directly by the researcher from the research subject or object and secondary data is not accumulated directly from the research object and subject. The results showed that there are three PAI learning strategies, namely PAI learning strategies for organizing PAI learning content, PAI learning delivery strategies and PAI learning management strategies. Thus, they are interrelated with each other in achieving learning objectives so that they can improve the quality of learning.